2014
DOI: 10.1111/acem.12390
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dyspnea Early in Acute Heart Failure: Patient Characteristics and Response Differences Between Likert and Visual Analog Scales

Abstract: Background Dyspnea is the most common symptom in acute heart failure (AHF), yet how to best measure it has not been well defined. Prior studies demonstrate differences in dyspnea improvement across various measurement scales, yet these studies typically enroll patients well after the ED phase of management. Objectives The aim of this study was to determine predictors of early dyspnea improvement for three different, commonly used dyspnea scales (i.e. five point absolute Likert scale, 10 cm visual analogue sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Another related finding was the lack of concordance between the scales. As discussed in a prior analysis, 10 such discordance suggests each scale may capture different aspects of this subjective symptom.…”
Section: Page 21 Of 29mentioning
confidence: 88%
See 1 more Smart Citation
“…Another related finding was the lack of concordance between the scales. As discussed in a prior analysis, 10 such discordance suggests each scale may capture different aspects of this subjective symptom.…”
Section: Page 21 Of 29mentioning
confidence: 88%
“…9 As a subjective, patient reported symptom, how exactly to assess and measure dyspnea continues to be debated. [9][10][11] While clinical trials now use a more standardized method of dyspnea assessment -formal training, standardized position, only after a period of rest 7 -use of dyspnea as a clinical trial endpoint has fallen out of favor, in part due to the difficulty of demonstrating a significant difference between investigational agents and usual care. 12,13 However, as the predominant AHF symptom, relief from dyspnea is important to patients.…”
Section: Introductionmentioning
confidence: 99%
“…The oral probenecid (Watson Pharmaceuticals, Parsippany, NJ) daily dose was 2 g (1 g twice per day), which based on previous publications corresponds to a mean serum concentration of 149 ng/mL 25. Prior dosing studies in animals revealed an EC50 of 49.33 mg/kg or ≈3 to 4 g daily for an average‐weight individual.…”
Section: Methodsmentioning
confidence: 99%
“…There are multiple dyspnea scales; those commonly used are the 5-point and 7-point Likert scales, and the 10-cm visual analog scale. A post-hoc analysis of URGENT (Ularitide Global Evaluation in Acute Decompensated Heart Failure) Dypsnea revealed that up to 40% of patients did not have improved dyspnea in the first 6 h; for those who did improve, patient characteristics differed across all 3 scales, with the c-index ranging from 0.71 to 0.83, suggesting that improvement in dyspnea may differ from scale to scale (43). The RELAX-AHF trial evaluating serelaxin used a visual analog scale area under the curve (VAS-AUC) endpoint to assess if serelaxin-treated patients would have improved dyspnea with baseline dyspnea, congestion on chest radiograph, elevated NP levels to Day 5 of the VAS-AUC, and the proportion of patients with moderate or marked dyspnea by the Likert scale during the first 24 h (44).…”
Section: Clinical Diagnosis Of Heart Failurementioning
confidence: 99%